2018
DOI: 10.1007/s11126-018-9598-z
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Stabilisation as a Sole Treatment Intervention for Post-Traumatic Stress Disorder in Southeast Asia

Abstract: Southeast Asia contains high numbers of traumatised populations arising from either natural disasters or interpersonal violence. Consequently, the need for empirically based trauma treatments, compromised by insufficiency in appropriately trained clinicians and mental health workers, makes the situation more challenging in addressing traumatic sequelae in local populations. In response, the humanitarian/ trauma capacity building organisation, Trauma Aid Germany, trained 37 therapists in psycho-traumatology, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Over the last 20 years, the development of EMDR Therapy in LMIC has occurred in response to humanitarian activity or targeted trauma capacity building in response to natural or human disasters (Adúriz et al 2009;Eichfeld et al 2019;Farrell et al 2011, Farrell and Keenan 2013, Farrell 2014Fernandez et al 2014;Gelbach and Davis 2007;Hasanovic 2016;Jarero et al 2008;Konuk and Zat 2015;Matthess et al 2019;Maxfield 2014;Mehrotra 2014;Shapiro 2012;Shapiro 2014aShapiro , 2014bSilver et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 20 years, the development of EMDR Therapy in LMIC has occurred in response to humanitarian activity or targeted trauma capacity building in response to natural or human disasters (Adúriz et al 2009;Eichfeld et al 2019;Farrell et al 2011, Farrell and Keenan 2013, Farrell 2014Fernandez et al 2014;Gelbach and Davis 2007;Hasanovic 2016;Jarero et al 2008;Konuk and Zat 2015;Matthess et al 2019;Maxfield 2014;Mehrotra 2014;Shapiro 2012;Shapiro 2014aShapiro , 2014bSilver et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Also, stabilization treatment might be more effective in different PTSD populations and settings. Eichfeld, Farrell (Eichfeld et al, 2018 ) for instance observed very large within-person effect-sizes and remission rates from stabilization-treatment for PTSD in a large study conducted in South-East Asia, albeit without a control condition. In that study, no clients had previous treatment-histories and the authors conclude that stabilization-treatment is effective, safe, and easily disseminated in post-conflict settings.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the results of previous investigations, these results indicate that stabilization groups should primarily be considered if preferred by the patient or if other evidence-based treatments are unavailable. Future studies could investigate if stabilization groups would be better applied to lower levels of care or in settings where large – scale training of therapist in trauma-focused treatments are difficult (Eichfeld et al, 2018 ). Investigations should also examine if stabilization-treatment can bolster treatment gains from later or concurrent trauma-focused treatment, and increase motivation for trauma-focused interventions in patients who are reluctant to engage in such treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This specific MHPSS intervention, informed by the mental health pyramid alluded to in the Inter-Agency Standing Committee (IASC) guidelines, 1 targets three levels of interventions-the level of the individual, the level of the group (of service users) and the level of the wider community. Broadly, the intervention is informed by empirically validated trauma treatment interventions, which include principles of psychoeducation, and stabilisation techniques based on trauma processing therapies such as Eye Movement Desensitization and Reprocessing (EMDR) Therapy (Eichfeld et al, 2018). This includes pilot projects implementing group EMDR Group Traumatic Episode Protocol (GTEP) therapy under the clinical supervision of international experts.…”
Section: Case Study Two: Yezidis In Iraqmentioning
confidence: 99%